When calls the heart. Year five [videorecording (DVD)] : 6-movie collection - Fearnley, Neill; Wood, Martin (Producer); Krakow, Erin; Hutton, Pascale; Wagner, Jack, 1959-; Oke, Janette, 1935- (Shout! Factory, 2018)
When Elizabeth leaves her comfortable life in the city to move to a frontier town, she finds new purpose and love.